2018
DOI: 10.15835/nsb10410382
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Diversity and Vegetation Analysis of Plants from Various Forest Types in Hosur Forest Division, Tamil Nadu, Southern India

Abstract: The study deals with the floristic diversity assessment and vegetation composition analysis in various forest types from Hosur Forest division situated in Eastern Ghats of Southern India, in the state of Tamil Nadu. The study recorded 468 species of plants belonging to 283 genera and 91 families, including Angiosperms (464 species), Pteridophytes (3 species) and Bryophytes (1 species). Of the total, 94 species are trees, 12 are lianas, 70 are shrubs, 34 species are climbers, 194 species are herbs, sedges 7, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Lantana camara invasions in natural communities are frequently linked to a reduction in species diversity as well as changes in ecosystem structure and function. Similar dominance of Lantana camara was also reported in moist deciduous forest of Odisha byReddy and Pattanaik (2009);Khanduri et al (2017);Tiwari and Ravikumar (2018) In herb layer the higher dominance was shown by Abutilon indicum (Fig.3a) which is due to survival, establishment and vigorous growth pattern of this species. The similar nding was given by Mohammed et al (2014) for Kanawa forest.…”
supporting
confidence: 81%
“…Lantana camara invasions in natural communities are frequently linked to a reduction in species diversity as well as changes in ecosystem structure and function. Similar dominance of Lantana camara was also reported in moist deciduous forest of Odisha byReddy and Pattanaik (2009);Khanduri et al (2017);Tiwari and Ravikumar (2018) In herb layer the higher dominance was shown by Abutilon indicum (Fig.3a) which is due to survival, establishment and vigorous growth pattern of this species. The similar nding was given by Mohammed et al (2014) for Kanawa forest.…”
supporting
confidence: 81%
“…Tree species richness of TTF is also higher than in some dry forest types of Tamil Nadu state. Tiwari and Ravikumar (2018) found 17, 20, 17, 13 and 14 tree species from Carnatic umbrella thorn, dry bamboo brake, Hardwickia, riverine and southern dry scrub forests, respectively. These forests are located within Hosur Forest Division, Tamil Nadu.…”
Section: Species Richnessmentioning
confidence: 96%
“…TTF acts as one of the homes for IUCNs' vulnerable tree species Chloroxylon swietenia which is represented by 45 individuals ha -1 . Earlier, Tiwari and Ravikumar (2018) observed the species from dry forests of Hosur Forest Division in Tamil Nadu. They recorded 27.8, 25.25 and 12.62 trees ha -1 from southern tropical dry mixed deciduous, Hardwickia and southern thorn scrub forests, respectively.…”
Section: Forest Tree Stand Densitymentioning
confidence: 99%
“…Mugger Crocodiles preying on Spotted Deer in the Cauvery River represents an unusual and intriguing phenomenon in predator-prey interactions. This stretch of the river lies in the Melagiri Hill Ranges, which form critical wildlife habitats between the Eastern and Western Ghats (Tiwari and Kaliamoorthy 2018). The river meanders through valleys and forests between the Cauvery Wildlife Sanctuary in Karnataka and the reserve forests of Hosur Forest Division in Tamil Nadu.…”
mentioning
confidence: 99%